A de novo heterozygous POU3F3 genotype for the p.(Q214*) variant in a fetus with transient isolated bilateral mild ventriculomegaly: a case report and review of the literature - Zhang, Hongyun; Linpeng, Siyuan; Teng, Yanling; Peng, Can; Liang, Desheng; Li, Zhuo; Wu, Lingqian (Frontiers in Pediatrics, 2023)
The prenatal prevalence of isolated ventriculomegaly is 0.039%–0.087%. Most isolated mild ventriculomegaly (MV) fetuses (>90%) have a favorable prognosis. However, 5.6% to 7.9% of fetuses with isolated MV have adverse neurodevelopmental outcomes. In this study, we reported the first case of prenatal Snijders Blok-Fisher syndrome (OMIM: #618604) caused by a truncating variant of POU3F3 (OMIM: *602480) in a fetus with transient isolated bilateral MV. The results of karyotype analysis, chromosomal microarray analysis, and TORCH infection evaluation for the fetus were all negative. However, a de novo likely pathogenic nonsense variant of NM_006236.3 (POU3F3): c.640C > T [rs1254251078] p.(Q214*) was identified by whole-exome sequencing (WES). Despite sufficient genetic counseling, the mother refused to undertake further brain magnetic resonance imaging (MRI) and decided to keep the fetus. She gave birth to a male infant through a full-term vaginal delivery. With a long-term follow-up, the infant unfortunately gradually presented with delayed motor development. The postnatal brain MRI of the proband showed dysplasia of the corpus callosum and ventriculomegaly. Considering the high probability of misdiagnosis for such cases, we further summarized the prenatal phenotypes from 19 reported patients with variants in POU3F3. The results revealed that 14 patients displayed a normal prenatal ultrasonographic manifestation, while only approximately 26.32% of fetuses showed MV or cysts without structural deformity. Thus our findings expand the variant spectrum of POU3F3 and suggest the importance of undertaking WES and brain MRI when the fetus has isolated bilateral MV.